2014
DOI: 10.1039/c3fo60630a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol on gut microbiota and fat storage in a mouse model with high-fat-induced obesity

Abstract: Recent studies have investigated the anti-obesity effect of resveratrol, but the pathways through which resveratrol resists obesity are not clear. In the present study, we hypothesize that resveratrol exerts anti-obesity effects that are likely mediated by mechanisms of regulating gut microbes, and in turn, improving fat storage and metabolism. Gut microbes, glucose and lipid metabolism in high-fat diet (HF) mice in vivo are investigated after resveratrol treatment. Several biochemical markers are measured. Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
207
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(238 citation statements)
references
References 47 publications
25
207
3
3
Order By: Relevance
“…The dosage used in the current experiment for resveratrol and quercetin was effective to decrease insulin levels and also, to improve insulin sensitivity, these findings support results from previous studies describing resveratrol and quercetin as potential candidates for the treatment of metabolic diseases such as insulin resistance [30,31]. To our knowledge, few studies have explored the effects of pure resveratrol and quercetin consumption alone or combined, on resident microbiota composition in order to find a possible association between their beneficial properties in the host and specific gut microbial modifications [55]. In contrast, there is strong evidence supporting the role of gut microbiota in several metabolic functions [56].…”
Section: Discussionsupporting
confidence: 72%
“…The dosage used in the current experiment for resveratrol and quercetin was effective to decrease insulin levels and also, to improve insulin sensitivity, these findings support results from previous studies describing resveratrol and quercetin as potential candidates for the treatment of metabolic diseases such as insulin resistance [30,31]. To our knowledge, few studies have explored the effects of pure resveratrol and quercetin consumption alone or combined, on resident microbiota composition in order to find a possible association between their beneficial properties in the host and specific gut microbial modifications [55]. In contrast, there is strong evidence supporting the role of gut microbiota in several metabolic functions [56].…”
Section: Discussionsupporting
confidence: 72%
“…Resveratrol has been reported to reduce the body weight of HFD-fed mice 6,7) via AMPK activation, 5) sirtuin activation, 6) adipogenesis inhibition, 7) or improvement of microbiota dysbiosis. 19) Piceatannol is relatively less well studied, although one report showed that piceatannol inhibits adipogenesis of 3T3-L1 preadipocytes. 20) Therefore, piceatannol is expected to also reduce the body weight of HFD-fed mice; however, there has been no in vivo study conducted to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…In another work, Qiao et al [61] found that resveratrol ameliorated the dysbiosis in the GM of mice induced by a high-fat diet. Specific effects included an increase in the FBR, significant inhibition of the growth of Enterococcus faecalis, and increased growth of Lactobacillus and Bifidobacterium.…”
Section: Effect Of Minor Food Compounds On the Human Gut Microbiotamentioning
confidence: 99%
“…Flavonols [57], quercetin [58,59], catechin and puerarin [59], anthocyanins [47], ellagitannins [60], resveratrol [61] and trans-resveratrol [58] are all reported to impact the activities of the GM. Quercetin supplementation resulted in an altered composition of the GM at different taxonomic levels, including the FBR and inhibiting the growth of bacterial species associated with diet-induced obesity, such as Erysipelotrichaceae, Bacillus spp., and Eubacterium cylindroides [58].…”
Section: Effect Of Minor Food Compounds On the Human Gut Microbiotamentioning
confidence: 99%